How the Readiness of Nature-Based Attraction During Pandemic Covid-19? Revisit the Implementation of the CHSE Certification - Andrianto, Tomy; Hutahaean, Agnes Fidela Agrefina; Susanto, Eko (Journal of Indonesian Tourism, Hospitality and Recreation, 2022)
ABSTRACTThis study aims to understand the readiness of nature-based attractions during the Covid-19 pandemic by revisiting the CHSE (Cleanliness, Health, Safety, and Sustainable Environment) certification the Indonesian government has implemented since 2020. Using a mixed-method approach, first, combining quantitative research by distributing surveys to visitors and qualitatively interviewing the operators of nature-based tourist attractions. This research was conducted from May to July 2021 in Greater Bandung, one of the favorite nature-based destinations in West Java, Indonesia. As a result, nature-based attractions are ready to receive visitors and can implement various health protocols but are asked to close when the virus spread rate is high again, even though there has never been a cluster. Furthermore, this research found that visitors and operators pay little attention to safety and a sustainable environment during a pandemic. Other highlights to maintain the Implementation of CHSE are strict monitoring by the government and, secondly, the operators' commitment to maintaining the supported facilities.ABSTRAKPenelitian ini bertujuan untuk mengetahui kesiapan objek wisata berbasis alam di masa pandemi Covid-19 dengan meninjau kembali sertifikasi CHSE (Cleanliness, Health, Safety, and Sustainable Environment) yang telah diterapkan pemerintah Indonesia sejak tahun 2020. Menggunakan pendekatan metode campuran, terlebih dahulu menggabungkan penelitian kuantitatif dengan menyebarkan survei kepada pengunjung dan wawancara kualitatif dengan operator tempat wisata berbasis alam. Penelitian ini dilakukan pada bulan Mei hingga Juli 2021 di Bandung Raya, salah satu destinasi berbasis alam favorit di Jawa Barat, Indonesia. Alhasil, objek wisata berbasis alam siap menerima pengunjung dan bisa menerapkan berbagai protokol kesehatan namun diminta tutup ketika tingkat penyebaran virus kembali tinggi, padahal belum pernah ada klaster. Selain itu, penelitian ini menemukan bahwa pengunjung dan operator kurang memperhatikan keselamatan dan lingkungan yang berkelanjutan selama pandemi. Sorotan lain untuk mempertahankan Implementasi CHSE adalah pengawasan ketat oleh pemerintah dan kedua, komitmen operator untuk memelihara fasilitas yang didukung.